Perempuan Berkarier dalam Perspektif Feminisme Radikal: Studi tentang Perempuan yang tidak menikah di Surabaya - Wulan, Nawang (Indonesian Democracy Research Center, 2025)
Social changes occurring in Surabaya, as the second largest city in Indonesia, have influenced women's roles in society, where more women are choosing to pursue careers rather than marry. This study aims to understand the factors influencing the decisions of women aged 25-40 in Surabaya to pursue careers. The method used is a qualitative approach with a phenomenological design, where data is collected through semi-structured interviews and non-participatory observations. The results indicate that higher education and financial stability empower women to reject marriage and reshape their views on existing social norms. Additionally, these findings suggest that educated women tend to be more independent and capable of making decisions based on their personal happiness. The conclusion of this study emphasizes the importance of understanding women's life choices in a modern context, as well as the need for policy support that promotes gender equality and job opportunities for women.